ANALYSIS SUPPLY CHAIN LOBSTER CATCH RESULTS PANULIRUS SPP AT THE BOJONGSALAWE FISH AUCTION PLACE (TPI) IN PANGANDARAN DISTRICT - hadi, ihda abdul; Nurhayati, Atikah; Andhikawati, Aulia; Maulina, Ine (Indonesian Fisheries Research Journal, 2025)
Lobster is one of the fisheries commodities with high economic value in Pangandaran Regency, especially at the Bojongsalawe Fish Auction Place (TPI). The high demand for lobster makes it one of the main sources of income for local fishermen. However, the efficiency of the lobster supply chain is still a challenge, especially in the aspects of product flow, information, finance and marketing margins at each distribution stage. This research aims to analyze the lobster supply chain at TPI Bojongsalawe using a quantitative descriptive approach. Data was obtained through primary and secondary analysis using interview methods and direct observation of fishermen, TPI managers, large traders, small traders and restaurant owners. The research results show that the lobster supply chain at TPI Bojongsalawe consists of seven chain structures which have different marketing efficiencies. The second marketing chain has the lowest marketing margin of IDR 80,000/kg or 40.47%, with a value fisherman share the highest was 76.34%, thus providing greater profits for fishermen. On the other hand, market share The largest was found in the seventh chain, where restaurants buy lobsters directly from fishermen, with a percentage reaching 58.49%. The main obstacles in the lobster supply chain include stock instability due to changes in weather conditions, significant price fluctuations, and a payment system that is not always done in cash. This has an impact on income uncertainty for fishermen and other market players. Therefore, a more efficient supply chain management strategy is needed, including the implementation of a centralized information system and increased coordination between market players. In this way, it is hoped that lobster distribution can be more optimal, fishermen's welfare will increase, and price stability will be better maintained.